Public Relations Strategy: Analysis of Social Media Utilization in Leadership Transition - Muhibuddin Muhibuddin; Nur Asia T; Fahma Islami; Encep Dulwahab (ETTISAL : Journal of Communication, 2025)
This study aims to examine Public Relations (PR) strategies in utilizing social media during the leadership transition period at State Islamic University Sultan Maulana Hasanuddin Banten for the 2025–2029 term. The analysis is grounded in Grunig and Hunt’s Four Models of Public Relations to examine patterns of internal communication. Drawing further on the Excellence Theory of Public Relations and Institutional Theory, this study explores how strategic communication practices are shaped by the normative ideal of two-way symmetrical communication while simultaneously being constrained by the bureaucratic structures of State Islamic Higher Education Institutions (PTKIN). This research employs a qualitative approach with a case study design. Data were collected through in-depth interviews with key stakeholders, including the elected rector, the head of the public relations bureau, senate members, lecturers, students, and local media representatives. Thematic analysis was used to identify patterns and meanings within the collected data. The findings indicate that the use of social media platforms such as Instagram, TikTok, Facebook, and Twitter/X is effective in supporting the university’s external image and contributes to crisis mitigation efforts. However, internal communication practices remain predominantly one-way, reflecting a gap between normative models of excellent public relations and institutional realities. Moreover, the absence of a structured crisis management protocol exacerbates perception gaps between the institution and the academic community.This study concludes that the effectiveness of strategic communication during leadership transitions is determined not only by careful planning but also by institutional capacity, particularly the competence of human resources and organizational readiness to anticipate and manage potential crises.